COVID-19 conundrum: clinical phenotyping based on pathophysiology as a promising approach to guide therapy in a novel illness. Issue 2 (27th August 2020) - Cherian, Robin; Chandra, Bharatendu; Tung, Moon Ley; Vuylsteke, Alain
We read with interest the recent editorial by Bos et al. [1] on the perils of premature phenotyping in coronavirus disease 2019 (COVID-19). The authors concluded that a normal compliance variant of acute respiratory distress syndrome (ARDS) does not exist, based on two small cohort studies reporting low respiratory system compliance in COVID-19 patients [2, 3]. However, this assumption may be erroneous, as, first, the admission and intubation thresholds are highly variable across units, resulting in marked heterogeneity. Secondly, several studies demonstrate that a high proportion of mechanically ventilated COVID-19 patients exhibit near-normal lung compliance [4–6]. The current evidence of COVID-19 pathophysiology supports the idea of specific phenotypes, and clinical phenotyping may be valuable to guide therapy https://bit.ly/2ZagmMn